Solitary fibrous tumor presenting as a colonic polyp: Report of a case and literature review - Roula Katerji; Diana Agostini-Vulaj (Elsevier, 2021)
Solitary fibrous tumor (SFT) is a rare mesenchymal tumor, which can be seen in varied anatomic locations, most commonly arising in the lung/pleura. SFTs of the gastrointestinal tract are exceedingly rare. Herein we report a case of SFT presenting as a 35 mm polyp in the descending colon, arising from the submucosa, that was found during routine screening colonoscopy in a 66 year old male. This was clinically felt to be a lipomatous lesion. Histologic sections demonstrated a spindle cell lesion with haphazard/patternless architecture, hyalinized collagen, and dilated, ectatic, irregularly shaped "staghorn" vessels. Mitoses were infrequent. Immmunostains demonstrated the neoplastic cells were positive for CD34 and STAT6; while they were negative for c-Kit, DOG1, SMA, and S100, confirming the diagnosis of SFT. The patient was disease free following the procedure. To our knowledge, this is only the second reported case of SFT presenting as a polyp, arising from the submucosal layer of the colon.